Integration of score systems, processing techniques, and value interpretation in learning evaluation - Haifa, Nisa; Arbeni, Wawan; Agustin, Ananda; Wulandari, Dwi Cahya; Kaila, Fakhra (EDUCTUM: Journal Research, 2026)
This study aims to analyze the integration of scoring systems, grade processing techniques, and interpretation of learning outcomes in elementary school learning evaluations. The methodology used is a literature study with a qualitative descriptive approach through a review of various scientific journals, educational evaluation books, and assessment instruments relevant to the latest curriculum. The results show that standardized scoring has a significant effect on increasing assessment objectivity. Furthermore, systematic grade processing techniques have been shown to improve the accuracy and consistency of learning evaluation results. Accurate grade interpretation helps teachers understand student learning development more comprehensively, allowing for more precise learning decisions that are oriented towards student needs. The conclusion of this study confirms that the integration of scoring, grade processing, and interpretation of learning outcomes needs to be implemented in a single, integrated assessment system to make learning evaluations more valid, reliable, and informative.